FEATURES OF CYTOKINE BALANCE AND IMMUMOGLOBULIN E CONCENTRATIONS IN THE PATIENTS WITH CHRONIC NEPHRITIS DEPENDING ON TREATMENT OUTCOMES - N. A. Fedicheva (SPb RAACI, 2014)
The paper presents comparative data concerning immunoglobulin E balance, as well as IL-4 and IFNγ amounts, in the patients with chronic nephritis with a favorable outcome vs. therapy failure after a standardized treatment. Results of treatment applied were evaluated by expert conclusions of the doctors, according to analysis of clinical and laboratory data. It has been shown that initial levels of IL-4 prior to the beginning of therapy were increased in the patients with inadequate response to therapy, as compared to healthy persons. Moreover, the patients with inadequate response to the treatment exhibited an increase in IgE concentrations and altered cytokine balance, thus suggesting a differentiation shift from naive Th to Th2 type, accompanied by development of allergic inflammation.